2020
DOI: 10.1002/clc.23414
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset atrial fibrillation and outcomes following isolated coronary artery bypass surgery: A systematic review and meta‐analysis

Abstract: Prior meta‐analyses have shown that new‐onset atrial fibrillation (NOAF) occurs in up to 40% of patients following cardiac surgery and is associated with substantial major adverse cardiovascular events. The stroke and mortality implications of NOAF in isolated CABG without concomitant valve surgery is not known. We thought that NOAF would be associated with increased risk of stroke and mortality, even in patients undergoing isolated CABG. A blinded review of studies from MEDLINE, CENTRAL, and Web of Science wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
2
28
0
1
Order By: Relevance
“…The time to new-onset of POAF ranged from 2 to 4 days after CABG. Although only four of the nine studies in our analysis reported on this outcome, the range agrees with previously published findings [ 8 , 12 ]. This is an important perioperative period which includes the patient awakening from anesthesia, extubation, and postoperative care for the prevention of pulmonary complications.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The time to new-onset of POAF ranged from 2 to 4 days after CABG. Although only four of the nine studies in our analysis reported on this outcome, the range agrees with previously published findings [ 8 , 12 ]. This is an important perioperative period which includes the patient awakening from anesthesia, extubation, and postoperative care for the prevention of pulmonary complications.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Zangrillo et al [ 23 ] included only patients who underwent isolated elective off-pump CABG and defined POAF as a condition detected by 12-lead EKG. Regardless of the variability among the included studies, the overall mean incidence of new-onset POAF of 32.4% across all participants is a matter of concern [ 8 , 14 ] which points to the need to reduce the incidence of POAF by building consensus to minimize technical variations in the procedure, such as use of CPB and correcting risk factors for POAF such as preoperative anemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that the incidence of POAF may decrease rapidly over time because the rate of AF detection markedly declined after the first 2 weeks of hospital discharge. However, previous studies 1,13,14,20,28 found an association between POAF and cardiovascular risk over longterm follow-up, when, presumably, POAF had largely resolved. Future research is needed to assess whether early anticoagulation may mitigate adverse short-term and long-term cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 92%